DEVELOPING ENGLISH READING MATERIALS FOR GRADE ELEVENTH STUDENTS IN SMK FARMASI YPFSU-MEDAN - Caterin Grace Ivana Siregar; Siti Aisah Ginting (Universitas Negeri Medan, 2018)
This research aimed to develop appropriate English reading materials for grade eleventh students in SMK Farmasi-YPFSU Medan. The research was conducted by Research and Development (R & D) design by adapting Borg and Gall’s research theory (2003) through six steps, such as: (1) Gathering data and information, (2) Analyzing data, (3) Designing new materials, (4) Validating new materials by experts, (5) Revising, and (6) Final product. The data of this research were the existing reading materials and the results of need analysis. The sources of the data were the textbook, students and teacher. The class consisted of 30 grade eleventh students. The instruments for collecting the data were questionnaire, interview, and documents. The questionnaire was analyzed as quantitative data and the interview result was analyzed as qualitative data. The questionnaire and interview was done to get the students’ need. The interview and questionnaire results prove that the students need English reading materials which cointain English for pharmacy program. Thus, developing English reading materials were procedure text. The developed procedure texts were related to the pharmacy program. The products have been validated by experts. The average scores are 4,03 from English Lecturer and 4,57 from English Teacher. It means the developing reading materials categorized as appropriate or relevant for the grade eleventh students in SMK Farmasi-YPFSU Medan.